A Season Long Investigation into Neck Strength Testing in Professional Men’s Rugby Union - DANIEL WALKER (2024)
AbstractGrowing global concern surrounds the long-term health consequences and brain injuries in rugby union players due to repetitive head impacts. Addressing and mitigating these risks is urgent. Prior research indicates that enhancing neck strength may potentially reduce head accelerations and the associated risk of brain injuries. This study focuses on neck strength as a potential factor in reducing head accelerations. Conducted over a nine-month period with 41 professional male rugby union players, the research began with two preliminary studies: a fatigue investigation trial to assess the impact of repeated testing, and a resistance priming study that explored short-term strength enhancements through targeted exercises. The main body of research comprised four sub-studies: a comparison of maximum neck strength in forwards versus backs, a two-month analysis of neck strength changes in these groups, an assessment of off-season effects on neck strength, and individual player case studies to explore specific responses.A bespoke isometric neck strength testing apparatus (INSTA) enabled consistent and reliable measurements. The fatigue investigation revealed minimal impact on test results, suggesting that the testing protocol did not induce significant fatigue. The resistance priming study demonstrated significant improvements in lateral flexion strength shortly after intervention, indicating potential for injury prevention.Forwards consistently showed greater neck strength than backs across all directions. During the two-month playing period, significant changes were noted only in the right lateral flexion for backs. No significant differences were found in neck strength between pre- and post-off-season measurements, suggesting stability in neck strength despite seasonal changes.The findings underscore the importance of enhancing neck strength to reduce head injuries and concussions in rugby union. Further research should aim to establish a standardised method for assessing neck strength, facilitating comparisons and improving injury prevention strategies.